INSTITUTIONAL BARRIERS AND DYSFUNCTIONS IN IMPLEMENTING ESG PRINCIPLES IN DIGITAL MANAGEMENT MODELS - ONOFRIICHUK, Oleg (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article examines institutional barriers and dysfunctions in implementing ESG principles within digital management models, with a particular focus on construction enterprises. ESG digitalisation is conceptualised as an institutionally driven transformation in which ESG goals move beyond communication and reporting to become managerial rules, procedures, and decision-making criteria. The study is grounded in an institutional approach and structural–logical modelling of relationships between the external regulatory–institutional environment, the internal corporate governance layer, and the digital management layer. A three-layer structure of ESG digitalisation is proposed, demonstrating that misalignments between these layers represent the root causes of persistent managerial dysfunctions. Five groups of institutional barriers are systematised (regulatory and standard-setting; organisational and managerial; data and verification; stakeholder coordination within the project ecosystem; and incentives and the managerial economics of ESG), and the mechanism through which they translate into typical dysfunctions of digital management models is explained. These dysfunctions include the “ESG showcase” effect, the data gap, the accountability gap, and conflicts between KPIs and incentives. For the construction sector, the article highlights the role of multi-actor project ecosystems and the project-based nature of operations, which intensify fragmentation of standards, data, and accountability and generate a persistent “cost/time versus ESG” criteria conflict. The practical value of the findings lies in defining priorities for the institutional reconfiguration of ESG digitalisation, including the development of ESG data governance, standardisation of metrics, formalisation of verification procedures, institutionalisation of accountability, and alignment of KPIs with ESG criteria as prerequisites for transforming digitalisation into measurable ESG performance.
Keywords: ESG; digital management; institutional barriers; managerial dysfunctions; construction enterprises; sustainable development; stakeholders